The Role of Employee Performance on Higher Education Performance in the Surakarta Batik Islamic University Environment - Muhammad Hafidz; Sudarwati; Bambang Mursito (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose wasto determine and explain the influence of leadership, compensation, work environment, and spirituality on teacher performance at the Al Hikmah Foundation, Boyolali. Materials and methods.The population of this study was 114 teachers at the Al Hikmah Foundation, and a sample of 114 teachers was selected using a saturated sampling technique. Data collection used a questionnaire. Data analysis used Multiple Linear Analysis Results.Leadership, Compensation, Work Environment, and Spirituality have a significant influence on teacher performance at the Al Hikmah Boyolali Foundation. This means that the variables of Leadership, Compensation, Work Environment, and Spirituality contribute 62.8% to teacher performance, while the remaining 37.2% is explained by other variables not included in this study. Conclusions.Leadership, Compensation, Work Environment, and Spirituality have a significant influence on teacher performance at the Al Hikmah Boyolali Foundation. This means that the variables of Leadership, Compensation, Work Environment, and Spirituality contribute 62.8% to teacher performance, while the remaining 37.2% is explained by other variables not included in this study.